2013
DOI: 10.1016/j.lwt.2013.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effect of UV-C, high intensity ultrasound and nonthermal atmospheric plasma treatments on reducing the allergenicity of α-casein and whey proteins

Abstract: Determining the effect of UV-C, high intensity ultrasound and nonthermal atmospheric plasma treatments on reducing the allergenicity of a-casein and whey proteins. Determining the effect of UV-C , high intensity ultrasound and nonthermal atmospheric plasma treatments on reducing the allergenicity of α-casein and whey proteins Abstract:Casein, β-lactoglobulin and α-lactalbumin are major milk protein allergens. The objective of this study was to investigate the effect of high intensity ultrasound, nonthermal at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 21 publications
(31 reference statements)
2
42
0
Order By: Relevance
“…[3,10,15] As shown in Figure 1, no significant changes were observed in the electrophoretic behaviour of β-Lg after ultrasound treatment compared with the control, indicating that β-Lg was still present after exposure to ultrasound without a change in molecular weight induced by protein degradation. Similar results have been obtained in the SDS-PAGE studies of ultrasonication-treated β-Lg, [21] ovalbumin, [19] and black bean protein isolate. [27] The band intensity of β-Lg had slightly decreased after UV-C treatment, especially the 30-min UV-C treatment (Figure 1).…”
Section: Sds-page Of β-Lgsupporting
confidence: 87%
See 2 more Smart Citations
“…[3,10,15] As shown in Figure 1, no significant changes were observed in the electrophoretic behaviour of β-Lg after ultrasound treatment compared with the control, indicating that β-Lg was still present after exposure to ultrasound without a change in molecular weight induced by protein degradation. Similar results have been obtained in the SDS-PAGE studies of ultrasonication-treated β-Lg, [21] ovalbumin, [19] and black bean protein isolate. [27] The band intensity of β-Lg had slightly decreased after UV-C treatment, especially the 30-min UV-C treatment (Figure 1).…”
Section: Sds-page Of β-Lgsupporting
confidence: 87%
“…[12] Ultrasound treatment Ultrasound treatment was carried out using a high-intensity ultrasound liquid processor (Zealway, China) operating at 40 kHz with an input power of 900 W. A 50 mL (2 mg/mL) of protein solutions in a 100-mL beaker were placed into the ultrasonic tank and treated for 15 or 30 min. [21] Water temperature fluctuation inside the ultrasonic bath was lower than 2°C during the treatment. After treatment, all samples were stored at -20°C until analysis.…”
Section: Uv-c Treatmentmentioning
confidence: 92%
See 1 more Smart Citation
“…More recently, nonthermal food processing technologies have emerged in the food industry due to their negligible effects on food properties (Huang, Hsu, Yang, & Wang, 2014;Shriver & Yang, 2011). Different studies have shown that nonthermal technologies such as high pressure processing (HPP) hold a great promise for the development of food ingredients with reduced allergenicity (Tammineedi, Choudhary, Perez-Alvarado, & Watson, 2013;Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…α-casein, β-lactoglobulin and α-lactalbumin) following irradiation with UV-C (Tammineedi et al, 2013).…”
Section: Allergenicitymentioning
confidence: 99%